Challenges for a Sustainable Food Production System on Board of the International Space Station: A Technical Review - Petronia Carillo; Biagio Morrone; Giovanna Marta Fusco; Stefania De Pascale; Youssef Rouphael (Agronomy, 2020)
The possibility of prolonging space missions—and consequently the permanence of humans in space—depends on the possibility of providing them with an adequate supply of fresh foods to meet their nutritional requirements. This would allow space travelers to mitigate health risks associated with exposure to space radiation, microgravity and psychological stress. In this review, we attempt to critically summarize existing studies with the aim of suggesting possible solutions to overcome the challenges to develop a bio-regenerative life support system (BLSS) that can contribute to life support, supplying food and O2, while removing CO2 on the International Space Station (ISS). We describe the physical constraints and energy requirements for ISS farming in relation to space and energy resources, the problems related to lighting systems and criteria for selecting plants suitable for farming in space and microgravity. Clearly, the dimensions of a growth hardware that can be placed on ISS do not allow to produce enough fresh food to supplement the stored, packaged diet of astronauts; however, experimentation on ISS is pivotal for implementing plant growth systems and paves the way for the next long-duration space missions, including those in cis-lunar space and to the lunar surface.